HUBUNGAN ANTARA GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN DI RSU PKU MUHAMMADIYAH GOMBONG - widodo, fatah (LPPM STIKES MUHAMMADIYAH GOMBONG, 2011)
Rumah Sakit Umum (GeneralÂ HospitalÂ )PKU Muhammadiyah Gombong is one hospital that is located at gombong district and one of Islamic hospital that belong to Muhammadiyah organization. The mission of Rumah sakit Umum PKU Muhammadiyah Gombong is to serve high health quality assurance services based on Islamic role including prevention, curative and rehabilitation. Furthermore, Rumah sakit Umum PKU Muhammadiyah Gombong offer health services for every people and duafa community. Some problems were faced since that hospital was established. One issues that commoly appeared is that low working motivation of hospital workers. It was appeared while they have to extend working time during a day. Mostly hospital workers were rejected due to several reasons. Therefore, it has an impact toward level of health quality assurance at PKU Muhammadiyah gombong. The aim of this study is to show relationship of different leader style towards work motivation. This study was descriptive survey with crosssectional approach. Sample was all hospital workers at RSU PKU Muhammadiyah Gombong. The number of respondents was 67 and chosen by random sampling method. Regresi linier analysis was used to show relationship of different leader style towards work motivation. The result show that six types leader style have significant relationship towards working motivation, on the other hand, six types leader style have no relationship towards work motivation at Rumah Sakit Umum PKU Muhammadiyah Gombong Â Keywords: working motivation, leader style, PKU Muhammadiyah Gombong